(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper examines the causal relationships between inflation, budget deficit, and money supply in Bangladesh from 1980 to 2023 using the Autoregressive Distributed Lag (ARDL) approach. Short-run causality analysis reveals unidirectional influences from budget deficits and money supply to inflation. Contrary to common conjectures that link budget deficits to inflation through increased money supply, our findings reveal no causality between money supply and inflation in both the short-run and long-run. The study contributes to the empirical literature by focusing on the unique economic context of Bangladesh, which has not been extensively explored in this tri variate relationship. The results suggest that conventional economic theories may not fully apply to developing countries like Bangladesh, where monetary expansions do not necessarily lead to inflationary pressures in the long run. The paper concludes with policy recommendations based on the analysis of the ARDL model and diagnostic tests confirming the model’s stability.